2020
DOI: 10.1002/bit.27622
|View full text |Cite
|
Sign up to set email alerts
|

Universal law for diffusive mass transport through mycelial networks

Abstract: Filamentous fungal cell factories play a pivotal role in biotechnology and circular economy. Hyphal growth and macroscopic morphology are critical for product titers; however, these are difficult to control and predict. Usually pellets, which are dense networks of branched hyphae, are formed during industrial cultivations. They are nutrient‐ and oxygen‐depleted in their core due to limited diffusive mass transport, which compromises productivity of bioprocesses. Here, we demonstrate that a generalized law for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 62 publications
(167 reference statements)
2
24
0
Order By: Relevance
“…In addition to the µCT assessment of real pellets from five industrial strains, it became also possible to compute such structures via Monte-Carlo growth simulations from scratch. The large set of computer-generated mycelial structures (> 3000) confirmed the generalised correlation of the effective diffusion coefficient with the porosity [ 31 ].…”
Section: Three Advances Of Research In the Last Decadementioning
confidence: 72%
See 1 more Smart Citation
“…In addition to the µCT assessment of real pellets from five industrial strains, it became also possible to compute such structures via Monte-Carlo growth simulations from scratch. The large set of computer-generated mycelial structures (> 3000) confirmed the generalised correlation of the effective diffusion coefficient with the porosity [ 31 ].…”
Section: Three Advances Of Research In the Last Decadementioning
confidence: 72%
“…With respect to modelling, a seamless multiscale integration of various approaches will become possible. Subcellular models form the basis of branching rates and branching directions to be used in Monte-Carlo simulations of pellet formation [ 31 , 49 , 50 ]. Such single pellet information needs to be transferred to a bioreactor scale, where the heterogeneity of different pellets with respect to pellet diameter, aspect ratio and surface solidity need to be accounted for.…”
Section: Three Areas Ripe For Developmentmentioning
confidence: 99%
“…A comprehensive study about the correlation between morphology and mass transport in filamentous fungi pellets is also available, written by Schmideder et al (2020) [31]. That cultivation in pellet form is less problematic for gas-liquid mass transfer and liquid mixing due to the lower viscosity of the fermentation broth has been reported in other studies [25,32,33].…”
Section: Morphology Of Penicillium Sp During Fermentationsmentioning
confidence: 98%
“…The key advantage of this novel μCT technique is thus the possibility to determine the exact inner structure of intact fungal pellets and to calculate the effective diffusion factor inside an A. niger pellet in relation to the hyphal fraction [84]. Remarkably, it was shown that the correlation between effective diffusion factor and hyphal fraction in fungal pellets follows a universal law, which is independent of micromorphological features like hyphal diameter, branching angle or interval and growth angle [85]. With this new tool, it is conceivable to calculate the actual nutrient or oxygen gradient within a pellet in a foreseeable future.…”
Section: How Can We Measure and Control Filamentous Growth And Macromorphology?mentioning
confidence: 99%